Draft Ninth Five Year Plan(1997-2002) and Annual Plan, 1997-98 Vol. II Statements (Excluding Statement III which is in Supplement of Volume II) - Planning Commission (Planning Commission, 1997)
Sub-Major-head wise Outlays and Expenditure Physical Targets and Achievements Externally Aided Projects - Outlays and Expenditure Externally Aided Projects - Physical Targets and Achievements Centrally Sponsored Schemes - Outlays and Expenditure Basic Minimum Services - Outlays and Expenditure Employment.
Government of Uttar Pradesh, State Planning Commission